2018
DOI: 10.1097/tgr.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Transcranial Direct Current Stimulation on Gait Kinematics of Individuals With Parkinson Disease

Abstract: Background: One of the most disabling problems in Parkinson disease (PD) is gait impairment. Noninvasive brain stimulation techniques, such as transcranial direct current stimulation (tDCS), have been introduced as a therapeutic alternative for coping with PD motor problems. However, the effects of tDCS on gait performance in PD have not yet been fully established. Therefore, the main objective of this study was to evaluate whether a single session of tDCS modifies gait kinematics in individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Thirteen studies had a PEDro score of 9 and 10, representing excellent quality [ 26 , 32 , 38 , 39 , 42 – 49 ], four studies had a score of 8 [ 50 53 ], and one study had a score of 7 [ 27 ]. Sixteen studies were designed double-blinded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies had a PEDro score of 9 and 10, representing excellent quality [ 26 , 32 , 38 , 39 , 42 – 49 ], four studies had a score of 8 [ 50 53 ], and one study had a score of 7 [ 27 ]. Sixteen studies were designed double-blinded.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were single-blinded but had otherwise good quality, as shown by a score of 8 [ 52 , 53 ]. Three studies reported dropouts without conduction of an intention-to-treat analysis [ 27 , 50 , 51 ]. In all studies, the allocation procedure was not described (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study tested in both off and on dopaminergic medication [ 33 ], one tested in the off state [ 49 ], and one did not report medication status [ 52 ]. Five investigations had open-label designs [ 38 , 43 , 45 , 46 , 47 ]; seven were parallel arm, randomized, double-blind, sham-controlled designs [ 33 , 40 , 41 , 42 , 44 , 50 , 52 ]; and eight were crossover, randomized, sham-controlled designs, with six being double-blind [ 36 , 37 , 39 , 48 , 49 , 51 ] and two with unstated blinding [ 34 , 35 ]. The tDCS intensities ranged from 1 to 2.8 mA (range of current densities = 0.02 mA/cm 2 –0.12 mA/cm 2 ) and stimulation was applied for 7–30 min (mode = 20 min).…”
Section: Resultsmentioning
confidence: 99%
“…Anodal tDCS may also induce dopamine release in the basal ganglia by the activation of glutamatergic corticostriatal fibers (Siebner et al, 1999;Fregni et al, 2006;Valentino et al, 2014). Studies have been done by targeting either the motor cortex (M1, 1-2 mA, 13-30 min) (Verheyden et al, 2013;Kaski et al, 2014b;Mak and Yu, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Fernandez-Lago et al, 2017;da Silva et al, 2018;Yotnuengnit et al, 2018) or the dorsolateral prefrontal cortex (DLPFC, 2 mA, 7-20 min) (Manenti et al, 2014;Lattari et al, 2017). At post-stimulation, a short-term benefit in gait was noted in most of these studies.…”
Section: Transcranial Direct Current Stimulation Idiopathic Parkinsonmentioning
confidence: 99%
“…• Gait and balance (Benninger et al, 2010;Verheyden et al, 2013;Capecci et al, 2014;Kaski et al, 2014a;Mak and Yu, 2014;Manenti et al, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Swank et al, 2016;Fernandez-Lago et al, 2017;Lattari et al, 2017;Criminger et al, 2018;da Silva et al, 2018;Dagan et al, 2018;Harris et al, 2018;Yotnuengnit et al, 2018;Alizad et al, 2019;Putzolu et al, 2019) • Upper limb function (Fregni et al, 2006;Benninger et al, 2010;Doruk et al, 2014;Salimpour et al, 2015;Costa-Ribeiro et al, 2016;Ferrucci et al, 2016;Schabrun et al, 2016;Cosentino et al, 2017;Ishikuro et al, 2018;Broeder et al, 2019) • Cognition (Nitsche et al, 2005;Boggio et al, 2006;Biundo et al, 2015;Manenti et al, 2016;Elder et al, 2017;Lawrence et al, 2018;Adenzato et al, 2019) • Impulsive pathological gambling behavior (Benussi et al, 2017a) • Speech (Pereira et al, 2013) • Sleep (Hadoush et al, 2018) • Fatigue …”
Section: Mode Of Tesmentioning
confidence: 99%